Analysis and design of a crash attenuator for a lightweight racing car. (2017) - Boria, Simonetta
In this paper, the crash safety performance of a racing car is evaluated focusing on the optimisation of its frontal impact attenuator from the geometrical and material point of view. After the definition of the CAD model of the full vehicle, it was possible to convert it into finite elements applying properties, materials, contacts, boundary and initial conditions for each body components in order to conduct a dynamic analysis through LS-DYNA code. The full vehicle front impact simulation against a rigid barrier is carried out considering different attenuator structures. With respect to the previous literary works, geometries taken into account are much more complex. Moreover, conventional and CFRP composite materials are used during modelling in order to do a comparison between them in term of safety. The results show that the composite attenuators can be more competitive than conventional absorbers of similar geometry in terms of intrusion and energy absorption.